In-vitro Sun Protecting Factor of Rice Bran Oil and Its Formulation as Compact Powder - Armini Syamsidi; Evi Sulastri; Yusriadi Yusriadi; Pramita Putri; Nuur Aanisah (Fakultas Farmasi Universitas Andalas, 2023)
This study aims to determine the effective concentration of rice bran oil which can protect against ultraviolet (UV) rays as well as formulate it in compact powder preparation followed by determination of its Sun Protecting Factor (SPF) value. Rice bran samples were extracted using the Soxhlet extraction method with n-hexane: ethanol (1:1) as the solvent. Further identification of the γ-oryzanol in rice bran oil was carried out using TLC silica gel GF254 with eluent of n-hexane:ethyl acetate (3:1). The obtained γ-oryzanol in rice bran oil was used as the ingredient to develop the compact powder which is made into five formulas with 0,05 %-0,25 % concentration. All formulas were characterized, including homogeneity, adhesion and crack test. UV-Visible spectrophotometry was used to determine the SPF value of rice bran oil and its compact powder. The identification results demonstrated a positive presence of the chemical γ-oryzanol in the rice bran oil. At concentrations of 500, 1000, 1500, 2000, and 2500 ppm, rice bran oil may protect against UV rays with SPF values ranging from 1.741 to 11.884. The result showed that all formulas dispersed homogeneously, performed well in terms of compactness, and had no breaks or cracks discovered. Meanwhile, the SPF values of all formulas are found to be 1.390 and 1.274. The results indicate that the SPF values are shallow and are included in the minimal SPF category (2-4) in protecting against UV rays.